Cyclic AMP Receptor Protein Acts as a Transcription Regulator in Response to Stresses in Deinococcus radiodurans - Yang, Su (PLoS One, 2016)
The cyclic AMP receptor protein family of transcription factors regulates various metabolic pathways in bacteria, and also play roles in response to environmental changes. Here, we identify four homologs of the CRP family in Deinococcus radiodurans, one of which tolerates extremely high levels of oxidative stress and DNA-damaging reagents. Transcriptional levels of CRP were increased under hydrogen peroxide (H(2)O(2)) treatment during the stationary growth phase, indicating that CRPs function in response to oxidative stress. By constructing all CRP single knockout mutants, we found that the dr0997 mutant showed the lowest tolerance toward H(2)O(2), ultraviolet radiation, ionizing radiation, and mitomycin C, while the phenotypes of the dr2362, dr0834, and dr1646 mutants showed slight or no significant differences from those of the wild-type strain. Taking advantage of the conservation of the CRP-binding site in many bacteria, we found that transcription of 18 genes, including genes encoding chromosome-partitioning protein (dr0998), Lon proteases (dr0349 and dr1974), NADH-quinone oxidoreductase (dr1506), thiosulfate sulfurtransferase (dr2531), the DNA repair protein UvsE (dr1819), PprA (dra0346), and RecN (dr1447), are directly regulated by DR0997. Quantitative real-time polymerase chain reaction (qRT-PCR) analyses showed that certain genes involved in anti-oxidative responses, DNA repair, and various cellular pathways are transcriptionally attenuated in the dr0997 mutant. Interestingly, DR0997 also regulate the transcriptional levels of all CRP genes in this bacterium. These data suggest that DR0997 contributes to the extreme stress resistance of D. radiodurans via its regulatory role in multiple cellular pathways, such as anti-oxidation and DNA repair pathways.